Antikeratinophilic activity of plant extracts: a review - AZIZ MOHAMMAD KHAN,; SEEMA BHADAURIA, (International Journal of Pharma and Bio Sciences, 2017)
Keratinophilic fungi and dermatophytes have been reported to cause infection of skin, hair and scalp, etc. The incidence of serious dermatophytic infection is a public health problem. The treatment of mycotic infection by increased use of antifungal agents has resulted in the development of resistance to these drugs. Therefore, it is necessary to discover new antifungal drugs from natural products. Plants are being utilized for thousands of years for food and to treat health disorders. Plants have been utilized for antimicrobial activities. Medicinal plants provide safe and effective treatment of these infections. The use of various herbal medicines for the treatment and prevention of mycotic infection has been studied worldwide in recent years. The aim of this paper is to review on the worldwide use of medicinal plants for the treatment of infectious mycotic diseases caused by keratinophilic fungi and dermatophytes. This review is an attempt to bring knowledge to every researcher to prefer medicinal plants over synthetic drugs.